The looming storm: Blood and cytokines in COVID-19 (2020)
A novel coronavirus termed as COVID-19 by WHO has been the causative agent of an unprecedented pandemic in the history of humanity. The global burden of mortality and morbidity associated with this pandemic continues to increase with each passing day as it is progressively leading to multiorgan dysfunction. In most cases, the cause of death has been attributed to respiratory failure, sepsis, cardiac failure, kidney injury, or coagulopathy. As more knowledge is being unfolded, an in-depth understanding of various systemic manifestations and complications of SARS-CoV2 is vital for optimum management of these patients. This novel virus is known to spread faster than its two ancestors, the SARS-CoV and Middle East respiratory syndrome coronavirus (MERS-CoV), demonstrating a case fatality ranging from 5-8% (1). Hematological abnormalities such as lymphopenia, thrombocytopenia, elevated D-Dimer, elevated fibrinogen, elevated fibrinogen degradation products as well as cytokines such as IL-6 are emerging as important prognostic marker for worse outcome of COVID-19. Among various systemic manifestations, hematological complications such as venous thrombosis causing pulmonary embolism or deep vein thrombosis, and arterial thrombosis causing myocardial infarction, strokes or limb ischemia are being noted to be directly linked to high mortality from COVID-19. An attempt to understand the pathophysiology of various hematological abnormalities including cytokine storm, hypercoagulable state and some rare presentations of this disease hence becomes imperative. Through this review, we aim to provide an up-to-date summary of current evidence-based literature of hematological manifestations, their consequences and management including role of anticoagulation and drugs targeting cytokine storm in patients with SARS-CoV-2.